PERTANGGUNGJAWABAN PELAKU TINDAK PIDANA TANPA HAK DAN MELAWAN HUKUM MENGGUNAKAN NARKOTIKA GOLONGAN I BAGI DIRI SENDIRI (Studi Putusan Pengadilan Negeri Binjai No. 182/Pid.B/2011/PN.BJ) - Ridho Mubarak; Dessy Agustina Harahap; Abdul Muin (Universitas Medan Area, 2014)
Any person who commits an offense or act which is contrary to law No 35of 2009 means having commited a criminal offense which is a great danger ofnarcotics for the life of nation. Abuse of drugs by adults could not be classed asa natural naughtiness, drug abuse is concern because the consequences will befelt in the perpetrator’s family. Moral damage means the fragility of nation’snational security and national defense. Narcotics is a related disasters asvictims of narcotic addiction is largely part of efforts to protect an save thenation.